2017
DOI: 10.1016/j.arr.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction in rodents: Caveats to consider

Abstract: The calorie restriction paradigm has provided one of the most widely used and most useful tools for investigating mechanisms of aging and longevity. By far, rodent models have been employed most often in these endeavors. Over decades of investigation, claims have been made that the paradigm produces the most robust demonstration that aging is malleable. In the current review of the rodent literature, we present arguments that question the robustness of the paradigm to increase lifespan and healthspan. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 207 publications
(265 reference statements)
5
95
0
3
Order By: Relevance
“…The impact of hyperphagia on shortening lifespan of subordinate mice can be understood in light of the established effect on longevity attributed to calorie restriction (CR) (Balasubramanian, Howell & Anderson, 2017; Mitchell et al., 2014). Although the maximal benefits of CR depend on several contextual factors (i.e., species and strain (Ingram & de Cabo, 2017)), CR attenuates age‐associated metabolic diseases allowing to preserve metabolic flexibility and limiting lipodystrophy and hepatic metabolic consequences (Mitchell et al., 2014). It can be speculated then that the same mechanisms altered by CR to extend longevity might become altered in an opposing way in subordinate mice resulting in aberrant lipid metabolism and dyslipidemia (Sanghez et al., 2013, 2016), compromising metabolic efficiency and accelerating physical wasting, overall contributing to earlier mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hyperphagia on shortening lifespan of subordinate mice can be understood in light of the established effect on longevity attributed to calorie restriction (CR) (Balasubramanian, Howell & Anderson, 2017; Mitchell et al., 2014). Although the maximal benefits of CR depend on several contextual factors (i.e., species and strain (Ingram & de Cabo, 2017)), CR attenuates age‐associated metabolic diseases allowing to preserve metabolic flexibility and limiting lipodystrophy and hepatic metabolic consequences (Mitchell et al., 2014). It can be speculated then that the same mechanisms altered by CR to extend longevity might become altered in an opposing way in subordinate mice resulting in aberrant lipid metabolism and dyslipidemia (Sanghez et al., 2013, 2016), compromising metabolic efficiency and accelerating physical wasting, overall contributing to earlier mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide unique leads for further studies that need to address optimal and feasible strategies for prolonged energy deprivation, with consideration of potential detrimental effects, such as an increased risk of infections or infertility. Naturally, evidence from animal models does not perfectly reflect the human situation [80] and caveats should be carefully considered in terms of feasibility, duration, timing and stringency of the CR conditions [81]. Therefore, it should be further explored how these strategies can be implemented in the human lifestyle and as such may contribute to healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, diet composition and genetic background have been thought to have a marginal impact on life-span extension elicited by CR. More recently, studies in mice and nonhuman primates have revealed that the effect of CR on life-span extension is not universal (20). Indeed, certain mouse recombinant inbred strains show either little increase or deleterious effects on life span after CR (5).…”
Section: Caloric Restrictionmentioning
confidence: 99%